ALISHER NAVOI’S “VAQFIYA” AND THE LITERARY-AESTHETIC FEATURES OF THE RUBAI WITHIN IT (American Journal of Interdisciplinary Research and Development, 2025)
In this article, we first analyzed the reasons for writing “Vaqfiya”, its intended purpose, and the concluding rubaiyat in the final part of the work, both in terms of form and content. The content of “Vaqfiya” is consistently and fluently expressed in the poetic style characteristic of Eastern classical literature. Since “Vaqfiya” is a work of an autobiographical nature, it reflects the author’s inner emotions, regrets, love for life and people, and attitude towards the environment in which he lived. “Vaqfiya” provides an opportunity to become closely acquainted with the personality of Alisher Navoi, and to learn what a person with strong faith and powerful will is like. The richness of the language in “Vaqfiya” with its elaborate comparisons, epithets, personification, poetic exaggeration, and unexpected analogies as well as its elevated praise, advice, and irony, all give the reader a deep impression of the topic and provide clear satisfaction. An important feature of Alisher Navoi’s creative activity appears to be that in each of his works, he rises higher than before in terms of artistry. The rubaiyat in “Vaqfiya” are a poetic interpretation of the prose content. Their impact is very powerful. In every line, the voice of the poet’s passionate soul can be heard. The mood and spirit described in them have acquired such power through their sincerity and truthfulness. The number of rubai in “Vaqfiya” are an integral part of Navoi’s poetry.